Detection of Virulence Genes and Relationship with Biofilm among Clinical Isolates of Acinetobacter Baumannii at a Tertiary Care Hospital in Dhaka City of Bangladesh (Bangladesh Journal of Medical Microbiology, 2025)
Background: Acinetobacter baumannii is mostly a cause of pneumonia, septicaemia, wound infections and urinary tract infections following hospitalization of patients with more severe illnesses. Adhesive virulence factors are considered an important factor in adhesion, tissue invasion, biofilm formation and survival of most bacteria and their virulence in human.Objective: The aim of the present study was detection of virulence genes among clinical isolates of Acinetobacter baumannii and to observe its relationship with biofilm.Methodology: This cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College and Hospital, Dhaka, Bangladesh over a period of one year from July 2015 to June 2016. Acinetobacter baumannii was isolated from different specimens and was identified and were screened for biofilm production by tissue culture plate method. Virulence genes such as fimH, sfa/focDE, afa/draBC, csgA, cnf1, cnf2, papC and kpsMTII were detected among isolated Acinetobacter baumannii by PCR.Results: A total 300 samples were studied of which 26 (8.7%) were Acinetobacter baumannii. Out of 26 isolated Acinetobacter baumannii, 15 (57.7%) were positive for fimH, 11 (42.3%) were positive for sfa/focDE, 9 (34.6%) were positive for afa/draBC, 12 (46.1%) were positive for csgA, 8 (30.8%) were positive for cnf1 and 6 (23.1%) were positive for cnf2 gene. papC and kpsMTII genes were not found among the isolated Acinetobacter baumannii strains. On testing by tissue culture plate method, from 26 isolated Acinetobacter baumannii, 16 (61.5%) were biofilm producers. Most of the virulence genes were more prevalent among biofilm producing Acinetobacter baumannii than non biofilm producer. A significant association was observed between fimH (p=0.02), sfa/focDE (p=0.05) and csgA (p=0.02) gene and biofilm formation in Acinetobacter baumannii.Conclusion: Among the isolated Acinetobacter baumannii, FimH, csgA, sfa/focDE and afa/draBC were the most commonly detected virulence genes. Most of the virulence genes were more prevalent among biofilm producing Acinetobacter baumannii than non biofilm producing Acinetobacter baumannii.Bangladesh Journal of Medical Microbiology, July 2024;18(2):63-68